Rejection of Former Shia Community in Sampang Perspective on Human Rights Law: Discourse of Religious Rights and Freedom in Indonesia - Mukhlis, Mukhlis; Jackson-Ortiz, Raphael D.; Jufri, Muwaffiq; Garunja, Evis; Aidonojie, Paul Atagamen (Universitas Negeri Semarang, 2023)
Tajul Muluk and 274 former Shia have not been able to return to their hometowns in Sampang District, even though they have pledged repentance to return to Sunni teachings on November 5, 2020. The formulated research problems consisted of: first, what was the position of former Shia adherents in Sampang District based on the perspective of rights and freedom of religion in Indonesia? And second, what was the form of violation of the right to freedom of religion in the case of community rejection of former Shia in Sampang District? This research utilizes empirical legal research methods combined with sociological and anthropological approaches. The research results concluded: First, the existence of former Shia adherents as refugees should be treated as a violation of the constitutional mandate of Indonesia which forbids acts of violence and violations of religious rights and freedoms, of all Indonesian citizens. Second that they were accused of embracing a deviant religious sect, is evidence to their religious minority status; and third the expulsion of the former Shia adherents was a violation of the right to freedom of religion. which had been regulated in the constitution, laws, and regulations under the constitution and the spirit of the Indonesian nation.